Evolution of RLSB, a nuclear-encoded S1 domain RNA binding protein associated with post-transcriptional regulation of plastid-encoded rbcL mRNA in vascular plants. Issue 1 (December 2016) - Yerramsetty, Pradeep; Stata, Matt; Siford, Rebecca; Sage, Tammy; Sage, Rowan; Wong, Gane; Albert, Victor; Berry, James
Abstract Background RLSB, an S-1 domain RNA binding protein ofArabidopsis, selectively bindsrbc L mRNA and co-localizes with Ribulose-1, 5-bisphosphate carboxylase/oxygenase (Rubisco) within chloroplasts of C3 and C4 plants. Previous studies using bothArabidopsis (C3 ) and maize (C4 ) suggest RLSB homologs are post-transcriptional regulators of plastid-encodedrbc L mRNA. While RLSB accumulates in allArabidopsis leaf chlorenchyma cells, in C4 leaves RLSB-like proteins accumulate only within Rubisco-containing bundle sheath chloroplasts of Kranz-type species, and only within central compartment chloroplasts in the single cell C4 plantBienertia . Our recent evidence implicates this mRNA binding protein as a primary determinant ofrbc L expression, cellular localization/compartmentalization, and photosynthetic function in all multicellular green plants. This study addresses the hypothesis that RLSB is a highly conserved Rubisco regulatory factor that occurs in the chloroplasts all higher plants. Results Phylogenetic analysis has identifiedRLSB orthologs and paralogs in all major plant groups, from ancient liverworts to recent angiosperms.RLSB homologs were also identified in algae of the divisionCharophyta, a lineage closely related to land plants.RLSB -like sequences were not identified in any other algae, suggesting that it may be specific to the evolutionary line leading to land plants. The RLSB family occurs in single copy across most angiosperms, although a few species with two copies were identified, seemingly randomly distributed throughout the various taxa, although perhaps correlating in some cases with known ancient whole genome duplications. Monocots of the order Poales (Poaceae and Cyperaceae) were found to contain two copies, designated here asRLSB- a andRLSB-b, with onlyRLSB-a implicated in the regulation ofrbc L across the maize developmental gradient. Analysis of microsynteny in angiosperms revealed high levels of conservation across eudicot species and for both paralogs in grasses, highlighting the possible importance of maintaining this gene and its surrounding genomic regions. Conclusions Findings presented here indicate that the RLSB family originated as a unique gene in land plant evolution, perhaps in the common ancestor of charophytes and higher plants. Purifying selection has maintained this as a highly conserved single- or two-copy gene across most extant species, with several conserved gene duplications. Together with previous findings, this study suggests that RLSB has been sustained as an important regulatory protein throughout the course of land plant evolution. While onlyRLSB-a has been directly implicated inrbc L regulation in maize, RLSB-b could have an overlapping function in the co-regulation ofrbc L, or may have diverged as a regulator of one or more other plastid-encoded mRNAs. This analysis confirms that RLSB is an important and unique photosynthetic regulatory protein that has been continuously expressed in land plants as they emerged and diversified from their ancient common ancestor.